Assessing the Implications of Ecological Civilization Pilots in Urban Green Energy Industry on Carbon Emission Mitigation: Evidence from China - Peng Zhang; Lei Tan; Fei Liu (Energies, 2023)
This study aims to explore the role of China’s Ecological Civilization Pilot Policies in carbon emissions reduction within the urban green energy industry. It further investigates how these policies influence carbon emissions. To achieve this, a unique incentive–constraint model is established considering China’s distinctive political system. The DID model was used in this study, employing Chinese city data spanning from 2009 to 2020 and analyzing urban panel data with the use of two specific policies as quasi-natural experiments. The analysis reveals the following key findings: (i) Ecological Civilization Pilot Policies in the energy industry substantially contribute to carbon emission reduction through the effects of technological progress and industrial structure optimization; (ii) the unique incentive–restraint mechanism within these policies enhances their effectiveness, with short-term incentives and carefully designed assessment criteria playing a pivotal role in their successful implementation. These findings carry substantial implications for shaping environmental policies within the energy industry, emphasizing the importance of such policies in the ongoing global effort to reduce carbon emissions and promote sustainability.